2021
DOI: 10.1021/acs.energyfuels.1c01850
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Binder-Free Peptide/Co(OH)2Nanohybrid Electrodes for Solid-State Symmetric Supercapacitors

Abstract: Organic–inorganic nanohybrids with diverse nanoarchitectures and intrinsic electronic properties are considered as efficient active materials for electrochemical charge storage applications. Herein, we have successfully electrodeposited peptide-based nanohybrids on carbon fiber paper (CP) substrates as the electrodes for the fabrication of symmetric supercapacitors (SCs). The electrodeposition technique has been used for in situ fabrication of a benzo­[2,1,3]­selenadiazole-5-carbonyl-protected BSeYY (BSe = ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…PVA/KOH was used as the electrolyte and the separator. It was then placed carefully inside a typical Swagelok cell setup for further electrochemical studies [33] . A schematic representation of the whole process is represented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PVA/KOH was used as the electrolyte and the separator. It was then placed carefully inside a typical Swagelok cell setup for further electrochemical studies [33] . A schematic representation of the whole process is represented in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…It was then placed carefully inside a typical Swagelok cell setup for further electrochemical studies. [33] A schematic representation of the whole process is represented in Figure 1. The potential window of À 0.2-0.4 V and the scan rate of 5-100 mV s À 1 was used to measure the cyclic voltammograms.…”
Section: Fabrication Of the Textile-based Supercapacitor Devicementioning
confidence: 99%
“…A recent review described the biomedical applications of such dynamic boronate esters cross-linked guanosine-quadruplex hydrogels . The supramolecular functional materials developed via the self-assembly of peptide biomolecules have been studied thoroughly over the past few years. The self-assembly of the peptide-based molecules including peptide bolaamphiphiles, aromatic N-terminal capped peptides, and short hybrid peptides led to the formation of different varieties of supramolecular nanostructures like vesicles, nanofibers, micelles, nanotubes, and ribbons. Therefore, these peptide-based supramolecular architectures find promising applications in various fields like drug delivery, cancer therapy, and tissue engineering. We envisioned the synthesis of an epitope assembled from a nucleobase and an amino acid resulting in biomaterial with a unique self-assembling behavior. Guanine, a purine nucleobase, potentially forms a G-quadruplex skeleton in the presence of suitable monovalent alkali metal ions because of the presence of multiple hydrogen bonding donor and acceptor sites.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the electrode only presented a lower specific capacitance of 19 mF cm –2 . Fortunately, coupling TiO 2 to remarkable conductivity materials is one of the most effective measures to optimize the conductivity of TiO 2 . , CF is one of the prime candidates due to its low cost and remarkable conductivity. However, due to its insufficient specific surface area (SSA), it is impractical to employ CF as an active ingredient for advanced energy storage devices. Both the activation and template methods are two of the most common efforts to increase the SSA. , For instance, Bonso et al prepared a flexible carbon fiber by the pyrolysis of electrospun polymers.…”
Section: Introductionmentioning
confidence: 99%